Crystalloid Prehydration versus Cohydration for Prevention Of Hypotension during Spinal Anaesthesia For Elective Caesarean Section - Sharma, Apurb; Gupta, P K; Singh, S N; Uprety, D (Health Renaissance, 2016)
Background: Hypotension during spinal anesthesia is a well known problem. Traditionally prehydration before the spinal block is one of the strategies used to prevent hypotension. Recently the efficacy of prehydration has been questioned. Objective: To compare the incidence of hypotension and vasopressor requirement with crystalloid prehydration and cohydration in women undergoing elective caesarean section. Methods: The prospective randomized study was carried out in 120 patients undergoing elective lower segment caesarian section under spinal anaesthesia. They were allocated to receive either 20ml/kg of lactated ringer’s solution during 20 minutes prior to induction of spinal anaesthesia (prehydration group) or equivalent volume by rapid infusion immediately after administration of the local anaesthetic intrathecally (cohydration group). Vitals, incidence of hypotension, dose of mephenteramine used and complications were recorded. Results: Hypotension occurred in 19 of 60 patients (31.6%) in prehydration group whereas in 15 of 60 patients (25.0%) in cohydration group, but the difference was not significant (P>0.05). But significantly less patients in the cohydration group (2 of 60 vs 18 of 60) developed hypotension and required vasopressor therapy before delivery of baby (P<0.001). Similarly, parturients in the cohydration group required significantly less dose of mephenteramine for treatment of hypotension. Conclusion: Rapid crystalloid administration after the induction of spinal anaesthesia for elective caesarean section prevents hypotension before delivery and decreases vasopressor requirement. Health Renaissance 2014;12(3): 190-196